Non-standard Spatial Statistics and Spatial Econometrics - Griffith, Daniel A.; Paelinck, Jean H. Paul (Advances in Geographic Information Science, 2011)
Despite spatial statistics and spatial econometrics both being recent sprouts of the general tree "spatial analysis with measurement"-some may remember the debate after WWII about "theory without measurement" versus "measurement without theory"-several general themes have emerged in the pertaining literature. But exploring selected other fields of possible interest is tantalizing, and this is what the authors intend to report here, hoping that they will suscitate interest in the methodologies exposed and possible further applications of these methodologies. The authors hope that reactions about their publication will ensue, and they would be grateful to reader(s) motivated by some of the research efforts exposed hereafter letting them know about these experiences.